The impact of green areas in higher education centers, case study “Campus Édison Riera” UNACH, Riobamba, 2024 - Luna Machado, Stephanie Gabriela (2025)
On April 13, 2011, the city of San Pedro de Riobamba was officially designated as Ecuador’s Polytechnic, University, and Technological City by the National Assembly, recognizing the contribution of its academic institutions to regional development. This designation has significantly influenced the urban, social, and environmental growth of the region. In this context, the present study examines the role of green areas in higher education institutions, using the “Edison Riera” campus of the Universidad Nacional de Chimborazo (UNACH), located in Riobamba, Ecuador, as a case study. A mixed-methods approach was adopted, combining quantitative and qualitative techniques, integrated with Geographic Information Systems (GIS) tools and perception surveys conducted with students, faculty, and administrative staff. The study involved classifying open spaces, identifying surface areas, evaluating their conservation status, and analyzing how these areas are perceived and used. The results revealed that the campus hosts 6,836 plant specimens, 72.24% of which are trees. Of these, 43.56% are in good condition. Survey participants indicated that these areas are essential to academic development, with stress reduction identified as the main benefit. This article emphasizes the relevance of green areas in university environments not only for their ecological value but also for their direct impact on academic performance and wellbeing. Furthermore, it provides key data to support the sustainable planning and management of campus green infrastructure. On April 13, 2011, the city of San Pedro de Riobamba was officially designated as Ecuador’s Polytechnic, University, and Technological City by the National Assembly, recognizing the contribution of its academic institutions to regional development. This designation has significantly influenced the urban, social, and environmental growth of the region. In this context, the present study examines the role of green areas in higher education institutions, using the “Edison Riera” campus of the Universidad Nacional de Chimborazo (UNACH), located in Riobamba, Ecuador, as a case study. A mixed-methods approach was adopted, combining quantitative and qualitative techniques, integrated with Geographic Information Systems (GIS) tools and perception surveys conducted with students, faculty, and administrative staff. The study involved classifying open spaces, identifying surface areas, evaluating their conservation status, and analyzing how these areas are perceived and used. The results revealed that the campus hosts 6,836 plant specimens, 72.24% of which are trees. Of these, 43.56% are in good condition. Survey participants indicated that these areas are essential to academic development, with stress reduction identified as the main benefit. This article emphasizes the relevance of green areas in university environments not only for their ecological value but also for their direct impact on academic performance and wellbeing. Furthermore, it provides key data to support the sustainable planning and management of campus green infrastructure.